2004
DOI: 10.1021/ma0491762
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Triggered Peptide Folding and Consequent Self-Assembly into Hydrogels with Tunable Modulus

Abstract: Intramolecular folding events, triggered by the presence of salt, induce the self-assembly of β-hairpin peptides into hydrogel networks at physiological conditions. At pH 7.4 and low ionic strength solution conditions, dilute, homogeneous solutions of peptide (≤2 wt %) exhibit the viscosity of pure water. Circular dichroism spectroscopy shows that, at pH 7.4 in the absence of salt, peptides are unfolded. By raising the ionic strength of the solution, electrostatic interactions between charged amino acids withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
446
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(472 citation statements)
references
References 47 publications
20
446
0
6
Order By: Relevance
“…61 It is necessary to initially have the molecule in a more solvated state than at the end. This can be achieved by heating to improve solubility, initially dissolving in a good solvent before adding an anti-solvent, choosing a pH at which the molecule is soluble and then adjusting the pH in one of a number of different ways to render the molecule less soluble, 62 adding a salt to charge screen, 63 using a pro-gelator with a cleavable, solubilizing group, 64 or using a chemical or enzymatic reaction to generate the gelator in situ from suitable precursors. 65,66 To the best of our knowledge, there are no examples where a molecule is simply added to a solvent and gelation results (although there are many examples where ''instant'' gelation can be induced by mixing two components that react or interact to form a gelator on contact).…”
Section: Process Of Assemblymentioning
confidence: 99%
“…61 It is necessary to initially have the molecule in a more solvated state than at the end. This can be achieved by heating to improve solubility, initially dissolving in a good solvent before adding an anti-solvent, choosing a pH at which the molecule is soluble and then adjusting the pH in one of a number of different ways to render the molecule less soluble, 62 adding a salt to charge screen, 63 using a pro-gelator with a cleavable, solubilizing group, 64 or using a chemical or enzymatic reaction to generate the gelator in situ from suitable precursors. 65,66 To the best of our knowledge, there are no examples where a molecule is simply added to a solvent and gelation results (although there are many examples where ''instant'' gelation can be induced by mixing two components that react or interact to form a gelator on contact).…”
Section: Process Of Assemblymentioning
confidence: 99%
“…Pochan and Schneider have demonstrated that short amphiphilic peptides that fold into β-hairpin structures will self-assemble into injectable hydrogels that can be used for tissue engineering [236][237][238][239][240][241][242][243][244][245]. The 20-amino acid peptide is composed of two sequences of alternating valine and lysine residues, which have a high propensity for β-sheet formation, adjoining a strong β-turn forming tetrapeptide (-V D PPT-).…”
Section: De Novo Designed β-Hairpin Polypeptidesmentioning
confidence: 99%
“…The 20-amino acid peptide is composed of two sequences of alternating valine and lysine residues, which have a high propensity for β-sheet formation, adjoining a strong β-turn forming tetrapeptide (-V D PPT-). The molecule is induced into an intramolecularly folded β-hairpin structure by various external stimuli including pH [236], temperature [237], salt [238], and light [240,244]. The alternating valine and lysine residues are oriented such that the molecule is amphiphilic and has one polar, lysine-rich face and one nonpolar, valine-rich face.…”
Section: De Novo Designed β-Hairpin Polypeptidesmentioning
confidence: 99%
“…Peptide self-assembly is driven by the orchestrated interaction of several intermolecular non-covalent forces including hydrogen bonding, π-π stacking, hydrophobic effect and electrostatic interactions. Environmental stimuli including pH [16][17][18][19], ionic strength and/or metal ions [18,[20][21][22], temperature [23], light [24] and enzyme-triggers [25], provide powerful approaches for modulating hydrogelation. Furthermore, introduction of microenvironment-sensitive amino acid residues into peptide sequences is also an important strategy for controlling peptide self-assembly and hydrogelation [9,[26][27][28].…”
mentioning
confidence: 99%